2023
DOI: 10.1161/circinterventions.122.012433
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Mechanical Aspiration Thrombectomy for High Thrombus Burden Coronary Vessel Occlusion: The Multicenter CHEETAH Study

Abstract: Background: Poor myocardial reperfusion due to distal embolization and microvascular obstruction after percutaneous coronary intervention is associated with increased risk of morbidity and mortality. Prior trials have not shown a clear benefit of routine manual aspiration thrombectomy. Sustained mechanical aspiration may mitigate this risk and improve outcomes. The objective of this study is to evaluate sustained mechanical aspiration thrombectomy before percutaneous coronary intervention in high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
(68 reference statements)
0
16
1
Order By: Relevance
“…TIMI 3 flow was more often achieved in the CHEETAH study compared with the present study, which could be attributed to inclusion of patients with late presentation (>12 h) in our study. 7 In our study technical success was lower in lesions that T A B L E 5 Summary of studies that investigated the outcomes with use of the Indigo CAT RX system. were previously treated with manual thrombectomy.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…TIMI 3 flow was more often achieved in the CHEETAH study compared with the present study, which could be attributed to inclusion of patients with late presentation (>12 h) in our study. 7 In our study technical success was lower in lesions that T A B L E 5 Summary of studies that investigated the outcomes with use of the Indigo CAT RX system. were previously treated with manual thrombectomy.…”
Section: Discussionmentioning
confidence: 58%
“…[3][4][5][6] The Indigo CAT RX Aspiration System (Penumbra Inc.) was designed to improve thrombectomy techniques by applying consistent vacuum. 7 Table 1 compares the Indigo CAT RX system and manual aspiration thrombectomy catheters. We examined the clinical and angiographic characteristics, as well as procedural techniques and outcomes of patients who underwent treatment with the Indigo CAT RX system at a large tertiary care hospital.…”
mentioning
confidence: 99%
“…This can be done safely in the left main or right coronary arteries as long as the guide catheter is coaxial. Devices that provide continuous powered aspiration may alleviate concerns of a thrombus dislodging inside the guide catheter and placed at risk of dislodging into the systemic circulation 8. Alternatively, a strategy of aspirating the thrombus deep inside the artery using a mother-and-child catheter allows entrainment of the thrombus and should help prevent dislodgement and embolisation 9…”
Section: Discussionmentioning
confidence: 99%
“…TIMI 3 flow was achieved in 90.2%, compared to 87% of TIMI 0 or 1 flow at baseline. 29 The CHEETAH study is a single-arm, prospective multicentre study of 400 patients with TIMI thrombus grade 4 or 5. Preliminary data showed that TIMI thrombus grade was 92.4% at grade 4-5 at baseline; this was improved to 72.8% at lower than grade 4 after thrombectomy, and 99.5% at grade 0 at the end of the procedure.…”
Section: Strategies To 'Fight' the Thrombusmentioning
confidence: 99%
“…30 In both series, no device-related serious adverse events were reported. 29,30 Another novel approach is mechanical thrombectomy using the Solitaire device (Medtronic), which has been shown to be safe and effective in the treatment of acute ischaemic stroke. Initial experience in a small cohort of patients showed that the device was applicable to intracoronary thrombus and was highly efficacious in reducing thrombus burden and improving TIMI flow in patients with high thrombus burden despite other conventional therapies.…”
Section: Strategies To 'Fight' the Thrombusmentioning
confidence: 99%